Linear quadratic gaussian (LQG) controller design for servo motor - Wan Mohd, Wan Syahidah (2013)
This paper presents the development of Linear Quadratic Gaussian controller design forDC servo motor.The accuracy of the control system is directly proportional to servo motor precision. However, the precision of DC servo motor system difficult to achieved due to the ignorance of the sensor noise and plant disturbance. Therefore LQG controller has been design to control speed and position of DC servo motor. In LQG controller designed, the noise sensor and plant disturbance has been considered as white noise Gaussian. This controller has be designed based on combination of Steady-state Linear Quadratic (LQ)OptimalControl and Steady-state Kalman Filter State Estimation by solving matrix Riccati equation in order to determine steadystate feedback gain, K and steady-state Kalman gain, G. MATLAB Simulink and MFile approached have been done to simulate the design. Besides that, Arduino microcontroller board also has been explored in order to do real-time Simulation between LQG controller and DC servo motor. The step response of closed-loop digital control system using LQG controller and opened-loop control system have been compared to verified that the performance of closed-loop control system better than opened-loop system